Islam, Budaya Indonesia, dan Posisi Kajian Islam di Perguruan Tinggi Islam - Mastuki HS (Khazanah: Jurnal Studi Islam dan Humaniora, 2017)
This article discusses the integration of Islamic values into Indonesians culture. Seen from the point of view of religion, Indonesia is the largest Muslim nation in the world ( the biggest Muslim country in the world). But in the religion - political and ideological, Indonesia is not an Islamic State .However, it does not mean Islam is Indonesia not original . Difficult to deny that the teachings and values of Islam has contributed much to the formation of Indonesian national culture. On the other hand, the institutionalization of Islamic values is also very powerful form of knowledge and intellectual system of the people, customs and belief systems, national culture, economic systems, up to the formation of Mus- lim behavior in Indonesia. In short, Islamic values has been fused with the culture of Indonesia. Islamic values have been institutionalized and becomes tradition in Indonesia then experience the dynamics and endless adjustments to this day.